Hukum Negara dan Hukum Adat: Dua Kutub yang Saling Menguatkan - Hasan Bachtiar Fadholi; Siska Diana Sari (CV. Era Digital Nusantara, 2022)
Abstract: Customary law is law formed from various Indonesian characters, most of which are not in the form of written rules. Meanwhile, State Law or National Law is a legal entity that was built to achieve the goals of the State which originates from the philosophy and constitution of the state, in both cases, it contains the goals, foundations, and ideals of the Indonesian state law. Purpose: The purpose of this research is to find out the existence of customary law in state law. Design/Methodology/Approach: This legal research is normative legal research conducted by researching library materials and is also known as library law research. Originality/value: This research seeks to review the relationship between customary law and state law, both of which depend on each other so that the existence of customary law is very important